USM SCHOOL OF HBP LECTURERS WON GOLD AND SILVER AWARD AT INDES 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 15 November 2016 Two entries from Universiti Sains Malaysia (USM) won Gold and Silver awards at the 5th International Innovation, Invention and Design (INDES 2016) Competition, which was held from 9th10th November 2016 at UiTM Seri Iskandar, Perak.